A Case Series on Pregnant Patients with Ovarian Cysts and Management of Potential Complications - Hermawan, Gezta Nasafir; Laihad, Bismarck Joel (Indonesian Journal of Obstetrics and Gynecology, 2025)
Abstract (English) Objective: To report a series of ovarian cyst cases in pregnancy that we diagnosed in our obstetrics and gynecology department; and to provide literary perspective in management of potential complications. Methods: A case series Case: We present three cases of pregnant patients with ovarian cysts diagnosed at different trimesters of gestational age. Patients included in this case series were shown to have cysts at the time of sonographic examination. Each patient displayed different complications and underwent specific management for each complication which includes laparotomy and emergency cesarean section. All patients were discharged in clinically stable conditions and the mass was evaluated for further histopathologic examination. This case series will also discuss possible complications of pregnancy with ovarian cysts, and the prevalence of each complication based on the gestational age. Due to its potential complications, ovarian cysts in pregnancy must be accurately evaluated and given appropriate management. Conclusion: Ovarian cysts in pregnancy must be evaluated accurately so that appropriate management is carried out. Clinicians should be aware of cyst complications during pregnancy. Keywords: Ovarian Cysts, Pregnancy, Potential Complications